Survey on Nursing Service Quality by SERVQUAL at Tehran Social Security Organization Hospitals - M Mohammadnia; B Delgoshaei; SH Tofighi; L Riahi; A Omrani (Tehran University of Medical Sciences, 2010)
Background: However nurses are responsible for patients quality care legally and ethically, in other side, patients have rights to receive appropriate and quality care. The aim of this descriptive study was to explore SERVQUAL dimensions (Reliability, Responsiveness, Assurance and Empathy) of Nursing Service Quality (NSQ) at Tehran Social Security Organization (SSO) Hospitals.Material and Methods: This study was carried out as an applied, descriptive and cross- sectional study during the summer and autumn of 2009 in Tehran SSO hospitals. Study tool was prepared on the basis of the standard and modified questionnaire of SERVQUAL based on Parasuraman, Zeithaml and Berry questionnaire (1988) for NSQ and consisted of 4 dimensions which were Reliability, Assurance, Empathy, and Responsiveness. The population for this study included of all inpatients of selected Tehran SSO hospitals who were selected by random sampling (N=200). For accounting Means, Standard Deviations and percents SPSS (ver. 16) have been used.Result:The total percentage of NSQ was upper middle (66), prescriptively Reliability (74), Assurance (69) and Empathy (64) were the most ones and Responsiveness (58) was the lowest. Conclusion: The results of this study showed that NSQ was in desired degree from patients` perspective in selected hospitals. The health care managers should have been attention to nursing as an important workforce of a hospital for raising the service quality of their organizations .Nurses are main role in quality care improvement and patients satisfaction. So, actions regarding to improve their performance are useful and necessary. Due to lowest score of Responsiveness among nursing staff, we suggest training courses for improving organizational culture on responding and effective communication to achieve high quality performance of all nursing group staff.